PENERAPAN PENDEKATAN SAINTIFIK SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 19 KOTO TINGGI - Febria Rahmi (Universitas Negeri Padang, 2017)
This study aims to improve science learning result in fourth grade of SDN Koto Tinggi, Tanjung Raya, Agam, through a Scientific Approach. This research is an action research using Kemmis and Mc.Taggart models which was conducted in two cycles. Each cycles consists of planning, implementation of action, observation, and reflection action. The results showed an increase in the results in learn science, especially in the topic of natural resources by using a scientific approach. This was proved by the average percentage of students in pre-cycle was 44.16% and increased to 63.33% after cycle I and 77.5% in cycle II. The implications of this study indicate that the use of a scientific approach makes the students more active and independent in learning with an integrated understanding. Teachers can develop an innovative approach that meets the needs of students, so the learning process will be more dynamic and meaningful.Keywords: Learning Result of Science; Scientific Approach; Action Research